Foundations of practical reason - Brandhorst, M (2007)
﻿ This thesis is an examination of the foundations of practical reason. Building on the later work of Wittgenstein, I argue for a subjectivist view of moral judgment and of judgments about reasons for action. On this view, moral judgments and judgments about reasons for action can be true or false, but they are not objective. The argument for this view has the form of an inference to the best explanation. Using a distinction between primary and secondary qualities, I suggest that moral judgments and judgments about reasons for action should not be construed as referring to an ethical or normative reality that exists independently of us. There are ethical facts and facts about our reasons, but these facts arise as the result of our involvement in a linguistic practice. This provides a new way of accounting for these judgments that differs both from moral realism and expressivism. The view of reasons that emerges is closely related to, but not identical with, reasons internalism as described by Bernard Williams. I reject his argument in favour of internalism and provide a new and independent argument to support this view of our reasons. In the course of spelling out that argument, I show why internalism as described by Williams should be modified, and why this does not commit us to externalism. In the final chapters, I show that there is an important parallel between our practical predicament and the account of our epistemic condition as portrayed by Wittgenstein. The inference to the best explanation is completed by considering a number of objections to subjectivism that are based on the idea that a subjectivist account of moral judgment and of reasons fails to do justice to the ethical phenomena. I reject these objections, and suggest that a subjectivist can both be reflectively aware of his subjectivism and continue to live well.